The Effectiveness of SBAR Communication in Improving the Completeness of Nurse Shift Reporting in Inpatient Wards - Herawati, Tri Mulia; Jubaidah, Siti (PT. Anagata Sembagi Education, 2025)
This study aims to examine the effectiveness of SBAR (Situation, Background, Assessment, Recommendation) communication in improving the completeness of nurse shift reporting in inpatient wards. Communication errors during handovers are one of the leading causes of mismanagement and adverse patient outcomes in hospitals. The use of SBAR offers a standardized and structured framework that enhances the clarity, accuracy, and relevance of information exchanged between nurses. Employing a quantitative approach with a one-group pretest-posttest design, this research was conducted in a general inpatient ward of a referral hospital. Data were collected using structured observation checklists to assess the completeness of shift reports before and after SBAR implementation. The results showed a significant increase in report completeness across all four SBAR components following the intervention. SBAR not only improved the structure and quality of communication but also strengthened professional accountability and patient safety. Therefore, SBAR is recommended for formal integration into standard operating procedures for nursing shift handovers in clinical settings.